Hubungan Regulasi Diri dalam Belajar dengan Keterampilan Berpikir Tingkat Tinggi Siswa pada Materi Sistem Gerak - Rusdi, Rusdi; Dewahrani, Yulilina Retno; Sholihah, Tsaniya (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
The student-centered learning process requires self-regulated learning students to optimize the learning process so that learning objectives to develop higher-order thinking skills can be achieved. This study aimed to investigate the correlation between self-regulated learning with students' high-order thinking skills on musculoskeletal system topics. This research used a descriptive correlational method with 106 students sample. The analysis technique used is simple regression and correlation test. The results showed that the correlation coefficient is 0.438, which means that there is a positive correlation between self-regulated learning and students' higher-order thinking skills in musculoskeletal system topics which is quite strong. This revealed as the self-regulation in learning increased, the students' higher-order thinking skills also increased. The coefficient determination result is 0.19 which means that self-regulated learning contributes 19% to higher-order thinking skills and 81% is supported by other factors. Recommendations for further research are that the implementation of data retrieval carried out boldly needs to be done by determining a certain time for each respondent and observing directly through video conferencing to reduce bias in the data results